Electrochemical study of β-Cyclodextrin binding with ferrocene tethered onto a gold surface via PAMAM dendrimers - Bustos,E. (2008)
This paper describes the tethering of ferrocene (Fc) onto polycrystalline gold electrodes by immobilized polyamidoamine (PAMAM) dendrimers films. The resulting electroactive surface provides a viable route for investigating quantitatively the host-guest binding of ferrocene with cyclodextrin (CD). In particular, electrochemical measurements reveal the effect of adsorbate-adsorbate interactions on the association constant K for the formation of the 1:1 βCDFc complex at the electrode-electrolyte interface. The results obtained from fitting the Frumkin isotherm to the adsorption data indicate that adsorbate-adsorbate interactions can have a strong impact on the βCD affinity for the ferrocenyl-modified surfaces studied here. The technique presented may be useful for investigating other host-guest binding reactions.